Critical Pedagogy and the Crisis of Humanization in Education: An Analysis of the Dehumanization of the Education System and Efforts for Restoration Through the Perspective of the Theology of Imago Dei - Emi Seli; Eny Oktavia (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Christian Religious Education (Pendidikan Agama Kristen / PAK) is called to be a human praxis that affirms the dignity of human beings as God's creation. However, in the context of modern education, PAK also faces a humanization crisis due to the dominance of instrumental paradigms, competition orientation, and cognitive achievement-based assessments that reduce students to objects of the system. This article aims to analyze dehumanization in the education system through a critical pedagogical perspective and to formulate PAK’s theological contribution in restoring human dignity based on the concept of imago Dei. This research uses a literature review method with a reflective-critical and interdisciplinary approach, integrating the critical pedagogical thought of Paulo Freire, Henry A. Giroux, and Peter McLaren with the theological reflections of Karl Barth and John R. Middleton. The results of the study show that an education system that emphasizes efficiency, quantitative evaluation, and structural compliance has implications for the alienation of students and weakens the spiritual and relational dimensions of education. Critical pedagogy provides a framework for liberation through dialogical and transformative education, while imago Dei theology affirms the ontological and ethical foundations of PAK as a restorative pedagogy. This article concludes that the integration of critical pedagogy and imago Dei theology strengthens the role of PAK as a liberating praxis of faith, restoring human dignity, and presenting an education oriented toward love, justice, and solidarity.